An Overview of the Networking Issues of Cloud Gaming: A Literature Review - Britanny Baldovino (Politeknik Negeri Cilacap, 2022)
With the increasing prevalence of video games comes innovations that aim to evolve them. Cloud gaming is poised as the next phase of gaming. It enables users to play video games on any internet-enabled device. Such improvement could, therefore, enhance the processing power of existing devices and solve the need to spend large amounts of money on the latest gaming equipment. However, others argue that it may be far from being practically functional. Since cloud gaming places dependency on networks, new issues emerge. In relation, this paper is a review of the networking perspective of cloud gaming. Specifically, the paper analyzes its issues and challenges along with possible solutions. In order to accomplish the study, a literature review was performed. Results show that there are numerous issues and challenges regarding cloud gaming networks. Generally, cloud gaming has problems with its network quality of service (QoS) and quality of experience (QoE). The poor QoS and QoE of cloud gaming can be linked to unsatisfactory latency, bandwidth, delay, packet loss, and graphics quality. Moreover, the cost of providing the service and the complexity of implementing cloud gaming were considered challenges. For these issues and challenges, solutions were found. The solutions include lag or latency compensation, compression with encoding techniques, client computing power, edge computing, machine learning, frame adaption, and GPU-based server selection. However, these have limitations and may not always be applicable. Thus, even if solutions exist, it would be beneficial to analyze the networking side of cloud gaming further.